Effect of Transcranial Direct Current Stimulation Combined With Patient-Controlled Intravenous Morphine Analgesia on Analgesic Use and Post-Thoracotomy Pain. A Prospective, Randomized, Double-Blind, Sham-Controlled, Proof-of-Concept Clinical Trial - Stamenkovic, Dusica M.; Mladenovic, Katarina; Rancic, Nemanja; Cvijanovic, Vlado; Maric, Nebojsa; Neskovic, Vojislava; Zeba, Snjezana; Karanikolas, Menelaos; Ilic, Tihomir V. (Frontiers in Pharmacology, 2020)
BACKGROUND Transcranial direct current stimulation (tDCS) is used for various chronic pain conditions, but experience with tDCS for acute postoperative pain is limited. This study investigated the effect of tDCS vs. sham stimulation on postoperative morphine consumption and pain intensity after thoracotomy. METHODS This is a single center, prospective, randomized, double blind, sham controlled trial in lung cancer patients undergoing thoracotomy under general anesthesia. All patients received patient controlled (PCA) intravenous morphine and intercostal nerve blocks at the end of surgery. The intervention group (a-tDCS, n=31) received anodal tDCS over the left primary motor cortex (C3-Fp2) for 20 mins at 1.2 mA, on five consecutive days; the control group (n=31) received sham stimulation. Morphine consumption, number of analgesia demands, and pain intensity at rest, with movement and with cough were recorded at the following intervals: immediately before (T1), immediately after intervention (T2), then every hour for four hours (Т3-Т6), then every six hours (Т7-Т31) for five days. We recorded outcomes on postoperative day one and five and conducted a phone interview inquiring about chronic pain one year later. (NCT03005548). RESULTS A total of 62 patients enrolled, but tDCS was prematurely stopped in six patients. 55 patients (27 a-tDCS, 28 sham) had three or more tDCS applications and were included in the analysis. Cumulative morphine dose in the first 120 hours after surgery was significantly lower in the tDCS [77.00(54.00-123.00) mg] compared to sham group [112.00(79.97-173.35) mg, p=0.043, Cohen’s d-0.42]. On postoperative day five, maximum VAS pain score with cough was significantly lower in the tDCS group [29.00 (20.00-39.00) vs. 44.50 (30.00-61.75) mm, p=0.018], and pain interference with cough was 80% lower [10.00 (0.00-30.00) vs. 50.00 (0.00-70.00), p=0.013]. One year after surgery, there was no significant difference between groups with regards to chronic pain and analgesic use. CONCLUSION In lung cancer patients undergoing thoracotomy, three to five tDCS sessions significantly reduced cumulative postoperative morphine use, maximum VAS pain scores with cough and pain interference with cough on postoperative day 5, but there was no obvious long-term benefit from tDCS.